Efektifitas Pelayanan dan Penyediaan Sarana/Prasarana dalam Meningkatkan Kualitas Pembelajaran Tingkat Sekolah Dasar Dilingkup Dinas Pendidikan Kabupaten Nabire - Randan, Ferry; A Todingbua’, Manuel; Buku, Atus (Journal of Comprehensive Science, 2025)
This study aims to analyze the services and provision of facilities/infrastructure in improving the quality of education at the elementary school level in the Education Office of Nabire Regency. Adequate facilities and infrastructure are crucial to support optimal learning processes. This research uses a qualitative approach with primary and secondary data obtained through observation, interviews, and documentation. The informants involved in this study are 5 employees of the Education Office of Nabire Regency who have knowledge about the provision of facilities/infrastructure at the elementary school level. The results of the study show that: 1) The effectiveness of services and the provision of facilities/infrastructure significantly impacts the quality of learning, although challenges such as slow administration processes, varying facility quality, and low community involvement still need to be addressed. 2) The condition of facilities and infrastructure at elementary schools faces various issues, including inadequate classrooms, a lack of teaching aids, poor sanitation, and limited access to technology, which need to be addressed comprehensively. 3) The Education Office of Nabire Regency has taken significant steps to improve the quality of education through teacher training, facility improvements, curriculum adjustments, increased community participation, and scholarship programs. Although challenges remain, these efforts are expected to positively impact students' academic development in the future. Hasil penelitian ini mengungkapkan bahwa: 1) Efektivitas pelayanan dan penyediaan sarana/prasarana di sekolah dasar di Kabupaten Nabire memiliki dampak signifikan terhadap kualitas pembelajaran. Meskipun terdapat kemajuan, tantangan seperti proses administrasi yang lambat, variasi kualitas fasilitas, kurangnya pemeliharaan, dan rendahnya keterlibatan masyarakat masih perlu diatasi. Oleh karena itu, diperlukan upaya yang lebih terintegrasi dan kolaboratif untuk memastikan semua siswa mendapatkan akses ke fasilitas yang memadai dan dapat belajar dalam lingkungan yang mendukung.